The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1111/j.1365-2923.2011.03930.x
|View full text |Cite
|
Sign up to set email alerts
|

Rewards, costs and challenges: the general practitioner’s experience of teaching medical students

Abstract: The findings extend reports in the previous literature by offering a richer description of current GP-teacher experience. Participants identified teaching rewards in a manner largely consistent with previous research, with the exception of enhanced practice morale and teamwork. Findings confirm that reduced productivity and increased time pressures remain key perceived negative impacts of teaching, but also reveal a number of other important costs and challenges. They emphasise the diversity of GP experience a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 20 publications
3
70
0
Order By: Relevance
“…1 Providing clinical placements can result in many benefits and challenges to healthcare services. Benefits include encouraging staff to engage in reflective practice 3 and increased exposure to evidence-based practice and current knowledge. 4 Reported barriers include managing time constraints and coping with challenging students.…”
Section: Introductionmentioning
confidence: 99%
“…1 Providing clinical placements can result in many benefits and challenges to healthcare services. Benefits include encouraging staff to engage in reflective practice 3 and increased exposure to evidence-based practice and current knowledge. 4 Reported barriers include managing time constraints and coping with challenging students.…”
Section: Introductionmentioning
confidence: 99%
“…Supervisors and instructor roles is very important factor on GPs. Studies have revealed that instructors can have either positive [35] or negative [36] impact on staff morale. Another factor is education place that most of medical students in Iran are educated in big cities.…”
Section: Discussionmentioning
confidence: 99%
“…While the expectation remains a reality, for most clinicians, having the ability to translate important learning points in an effective way, remains a challenge (Sturman et al 2011). McDougall and Drummond (2005) reiterate that although doctors are experts at what they teach, they lack the expertise on how to teach and often continue to depend on personal experience rather than educational skill.…”
Section: Introductionmentioning
confidence: 99%